Fault analysis to Determine Deformation History of Kubang Pasu Formation at South of UniMAP Stadium Hill, Ulu Pauh, Perlis, Malaysia - Suryadi, Adi (UIR PRESS, 2016)
The Kubang Pasu Formation at South of UniMap Stadium Hill has suffered deformation that produced fault with various types and orientations. First deformation (ST1) is southeast â northwest were resulted normal, reverse, dextral and sinistral fault. At station 32, Reverse fault (N940E/480) from ST1 was cut by reverse fault (N480E/400) result of second deformation (ST2). Another cross cutting fault found at station 108, third deformation (ST3) with stress direction from northeast â southwest that produced reverse fault with strike direction N1340E and 680 of dip angle was cutting the reverse fault (N870E/660) from second deformation. The youngest deformation (ST4) has stress from east â west. At station 110, normal fault (N900E/300) is representing the youngest deformation was cutting the reverse fault (N1540E/520) from third deformation.